2022
DOI: 10.3233/jpd-212892
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Longitudinal Change of Motor, Non-Motor, and Biological Features in Early Parkinson’s Disease

Abstract: Background: Investigation of sex-related motor and non-motor differences and biological markers in Parkinson’s disease (PD) may improve precision medicine approach. Objective: To examine sex-related longitudinal changes in motor and non-motor features and biologic biomarkers in early PD. Methods: We compared 5-year longitudinal changes in de novo, untreated PD men and women (at baseline N = 423; 65.5%male) of the Parkinson’s Progression Markers Initiative (PPMI), assessing motor and non-motor manifestations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
6
17
0
Order By: Relevance
“…A complex set of differences emerged from the comparison of gender‐related phenotypes. We found a slightly older AAO and milder motor symptoms in women, which was consistent with previous work 25‐27 suggesting a more benign PD motor phenotype in women than in men. Women had a higher rate of developing levodopa‐induced dyskinesias, which is in agreement with previous studies 28,29 .…”
Section: Discussionsupporting
confidence: 92%
“…A complex set of differences emerged from the comparison of gender‐related phenotypes. We found a slightly older AAO and milder motor symptoms in women, which was consistent with previous work 25‐27 suggesting a more benign PD motor phenotype in women than in men. Women had a higher rate of developing levodopa‐induced dyskinesias, which is in agreement with previous studies 28,29 .…”
Section: Discussionsupporting
confidence: 92%
“…Recently, new data on gender differences in PD were obtained from the Parkinson’s Progression Markers Initiative (PPMI) database, an international, multiple-site, prospective, longitudinal cohort study. A 5-year longitudinal analysis of a subgroup of 423 patients (65.4% men) from the PPMI cohort showed: (a) a similar increase over time of MDS-UPDRS part III OFF scores in both sexes, with an increase over time of MDS-UPDRS part III ON scores only in men; (b) a significant increase over time in Levodopa equivalent dose (LED) in men as compared to women [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Picillo, 1 [9] Longitudinal study (data obtained from the PPMI database) (2) lower tremor scores in coffee drinkers are found in both the male and female subgroups;…”
Section: Namentioning
confidence: 99%
“…Incidence and prevalence of PD are between 1.5 and 2 times higher in men than in woman and disease onset in women is slightly later than in men [ 3 , 4 ]. Clinically, males have more rigidity and speech problems, whereas females seem to have a greater prevalence of dyskinesia and motor and non-motor response fluctuations but more mild motor deterioration [ 5 , 6 , 7 ]. Regarding non-motor symptoms (NMSs), some studies have observed that symptoms such as fatigue, depression, anxiety, and sleep problems are more frequent in females, whereas other NMSs such as drooling, diurnal somnolence, urinary and sexual dysfunction, and cognitive problems are more prevalent in males [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%